Influence of climate and external plaster on the humidity conditions of masonry walls - R. A. Gorshkov; S. V. Kornienko (Vestnik MGSU)
Introduction. The study was carried out to determine the possible causes of damage to the finishing plaster coverings on the facades of historical stone buildings, built in St. Petersburg before 1917, as a result of their humidification and subsequent frost destruction.Materials and methods. The mechanism of humidification of a homogeneous wall structure plastered on both sides due to the moisture transfer from the room to the environment through the wall thickness due to the difference in partial pressures of water vapour from inside and outside the room during the cold season is studied. The paper provides the graphs of the distribution of the actual and maximum partial pressures of water vapour over the thickness of the wall structure, depending on the type of plaster covering, for two calculated cases — for the conditions of the coldest month and the coldest five-day period in St. Petersburg.Results. It is revealed that for the conditions of the coldest month in St. Petersburg, the actual partial pressure of water vapour in the thickness of the wall structure under consideration does not exceed the maximum, which indicates the absence of conditions for moisture condensation in the thickness of the wall envelope. However, as the vapour permeability of the external plaster decreases, the curves of the distribution of the actual and maximum partial pressures converge at the interface of the stone base and the plaster covering. For the conditions of the coldest five-day period, the actual partial pressure of water vapour already at a distance of 135 mm from the inner surface exceeds the maximum partial pressure, which indicates a high risk of moisture condensation, and this risk is the higher the less vapour permeable the plaster covering is.Conclusions. It is proven that when the coldest outdoor temperatures are established, there is a high probability of condensation of water vapour in the thickness of the wall structure under consideration. The highest risk of freezing of the condensable moisture will be observed at the interface of stone base with the external plaster. Freezing of moisture in cracks and voids in the contact zone of the stone base and the plaster covering can lead to water trapping, the occurrence of significant internal stresses in the finishing layer and, as a result, to its gradual damage, up to the loss of individual fragments of plaster.